Mapping the Intersection of Financial Technology and Sustainability: A Bibliometric Analysis Using R Programming Language - Rafiqoh; Muh. Irfandy Azis; Erick Karunia; Ang Hong Loong; Nursia (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Financial technology has transformed the global financial landscape, while sustainability has become a critical priority for addressing environmental and economic challenges. This study aims to examine the research landscape at the intersection of financial technology and sustainability through bibliometric analysis. Using the R programming language and data from the Scopus database spanning 2017 to 2025, the analysis maps publication trends, influential contributors, and collaboration patterns. Key findings reveal dominant themes such as green finance, digital banking, climate change, and environmental policy, reflecting a convergence of economic and environmental priorities. Leading journals include Resources Policy and Sustainability (Switzerland), with significant contributions from scholars. Strong international collaborations, particularly involving China, India, and Brazil, highlight regional efforts in sustainable financial innovation. The study concludes that financial technology plays a vital role in advancing sustainable finance and financial inclusion, though gaps in global representation and methodological diversity persist. Future research should focus on integrating artificial intelligence, blockchain, and broader regional perspectives, particularly from underrepresented areas like Africa, to enhance sustainable financial systems.